Bridging the Expository Literacy: The Effectiveness of the SQ4R Method Based on Local Wisdom SDGs in Addressing Comprehension Deficits in Elementary School Students - Nurjannah, Mita Sukma (International Conference on Elementary Education, 2025)
This research is motivated by a deficit in expository literacy skills among elementary school students, reflected in their low ability to read comprehension and write structured and logical expository texts. This deficiency represents a gap that needs to be addressed to support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4 on Quality Education. This study aims to test the effectiveness of the SQ4R (Survey, Question, Read, Recite, Reflect, and Review) method, integrated with local wisdom values relevant to the SDGs, in improving these two skills. The study used a quasi-experimental method with a nonequivalent control group design. The subjects were fifth-grade elementary school students, divided into an experimental group receiving the SDGs-based SQ4R treatment and a control group using conventional methods. Data were collected through reading comprehension tests and expository writing performance tests, and analyzed using t-tests to compare learning outcomes between groups. The results showed significant improvements in the experimental group compared to the control group, both in reading comprehension and expository writing skills. Integrating local wisdom (e.g., the values of mutual cooperation and nature conservation) into the SQ4R stages can increase the relevance of the material, helping students absorb and reflect on the information more deeply. Therefore, it can be concluded that the SQ4R method based on SDGs Local Wisdom is effective in bridging the literacy gap and is an innovative learning method that supports sustainable education at the elementary level.